Strategies for Drug Encapsulation and Controlled Delivery Based on Vapor‐Phase Deposited Thin Films. Issue 3 (19th September 2017) - Perrotta, Alberto; Werzer, Oliver; Coclite, Anna Maria
Abstract : Vapor‐phase deposition methods allow the synthesis and engineering of organic and inorganic thin films, with high control on the chemical composition, physical properties, and conformality. In this review, the recent applications of vapor‐phase deposition methods such as initiated chemical vapor deposition (iCVD), plasma enhanced chemical vapor deposition (PE‐CVD), and atomic layer deposition (ALD), for the encapsulation of active pharmaceutical drugs are reported. The strategies and emergent routes for the application of vapor‐deposited thin films on the drug controlled release and for the engineering of advanced release nanostructured devices are presented. Abstract : Vapor‐phase deposition methods allow the synthesis of (in)organic thin films, with high control on the chemical‐physical properties and conformality. In this review, the encapsulation strategies of active drug molecules by means of vapor phase deposition processes are reported. The effects of (pre‐) treatment and thin film deposition on controlled drug release and morphology are also reviewed, together with future perspectives and 'smart' device applications.